1994
DOI: 10.1002/app.1994.070540202
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability studies of a polyimide–polytetrafluoroethylene blend and its components

Abstract: Low‐dielectric constant (ϵr) polymers, such as polytetrafluoroethylene (PTFE), are an important component of advanced electronic products that transit data, since it is this physical property that largely determines a device's performance. For instance, the dielectric constant determines overall signal speed and proximity in that one circuit line can be placed to another, i.e., wiring density, while maintaining desired electrical characteristics. However, due to PTFE's inertness and intractability, significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The melt temperature ( T m ) of PTFE/PI is 330.0°C as shown in Fig. b, which is similar with the literature value . T m of PTFE/SiO 2 ‐PI and PTFE/porous‐PI composites are in the range of 325.3–325.6°C and 326.6–327.1°C, respectively.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The melt temperature ( T m ) of PTFE/PI is 330.0°C as shown in Fig. b, which is similar with the literature value . T m of PTFE/SiO 2 ‐PI and PTFE/porous‐PI composites are in the range of 325.3–325.6°C and 326.6–327.1°C, respectively.…”
Section: Resultssupporting
confidence: 86%
“…In addition, the uneven surface of polymer composites decreases the contact area between polymer composites and counterpart ball. Lower friction contact area contributes to the decrease in COF and wear rate . Thus, the tribological performance of PTFE/porous‐PI composites is better than that of PTFE/PI.…”
Section: Resultsmentioning
confidence: 99%
“…Some important PTFE blends and composites were reported in the literature with polyacetal (POM), 27,28 PE, 29 -33 polyimide, 34 poly(ethylacrylate), 35 and poly(etheretherketone). 36 In all these studies, some properties were found to be improved such as mechanical, thermal, and wear resistance of the corresponding blend and composite application of PTFE.…”
Section: Introductionmentioning
confidence: 98%